An Enhancement on EASR Method for Sink Relocation in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
In a wireless sensor network (WSN), how to conserve the limited power resources of sensors to extend the network lifetime of the WSN as long as possible while performing the sensing and sensed data reporting tasks, is the most critical issue in the network design. In a WSN, sensor nodes deliver sensed data back to the sink via multi hopping. The sensor nodes near the sink will generally consume more battery power than others; consequently ,these nodes will quickly drain out their battery energy and shorten the network lifetime of the WSN. Sink relocation is an efficient network lifetime extension method, which avoids consuming too much battery energy for a specific group of sensor nodes. Energy Aware Sink Relocation (EASR) is a sink relocation mechanism for mobile sinks in WSNs. The mechanism uses information related to the residual battery energy of sensor nodes to adaptively adjust the transmission range of sensor nodes and the relocating scheme for the sink. The EASR scheme mainly focuses on when the sink will be triggered to perform the relocation process and where to move to. Here routing is based on remaining energy of the sensor nodes in the path. To achieve this type of routing, here used Maximum Capacity Path (MCP) Algorithm. Sink Relocation mechanism consists of two parts. The first is to determine whether to trigger the sink relocation by determining whether a relocation condition is met or not. The second part is to determine which direction the sink is heading in and the relocation distance as well. By adding clustering to the topology of the EASR scheme the delay in the transmission can be reduced. Also the neighbouring nodes of the sink are not always be busy. So the network lifetime can also be increased.